A gene edited pig model for studying LGR5+ stem cells: implications for future applications in tissue regeneration and biomedical research - Hill, Amanda B. T.; Murphy, Yanet M.; Polkoff, Kathryn M.; Edwards, Laura; Walker, Derek M.; Moatti, Adele; Greenbaum, Alon; Piedrahita, Jorge A. (Frontiers in Genome Editing, 2024)
Recent advancements in genome editing techniques, notably CRISPR-Cas9 and TALENs, have marked a transformative era in biomedical research, significantly enhancing our understanding of disease mechanisms and helping develop novel therapies. These technologies have been instrumental in creating precise animal models for use in stem cell research and regenerative medicine. For instance, we have developed a transgenic pig model to enable the investigation of LGR5-expressing cells. The model was designed to induce the expression of H2B-GFP under the regulatory control of the LGR5 promoter via CRISPR/Cas9-mediated gene knock-in. Notably, advancements in stem cell research have identified distinct subpopulations of LGR5-expressing cells within adult human, mouse, and pig tissues. LGR5, a leucine-rich repeat-containing G protein-coupled receptor, enhances WNT signaling and these LGR5+ subpopulations demonstrate varied roles and anatomical distributions, underscoring the necessity for suitable translational models. This transgenic pig model facilitates the tracking of LGR5-expressing cells and has provided valuable insights into the roles of these cells across different tissues and species. For instance, in pulmonary tissue, Lgr5+ cells in mice are predominantly located in alveolar compartments, driving alveolar differentiation of epithelial progenitors via Wnt pathway activation. In contrast, in pigs and humans, these cells are situated in a unique sub-basal position adjacent to the airway epithelium. In fetal stages a pattern of LGR5 expression during lung bud tip formation is evident in humans and pigs but is lacking in mice. Species differences with respect to LGR5 expression have also been observed in the skin, intestines, and cochlea further reinforcing the need for careful selection of appropriate translational animal models. This paper discusses the potential utility of the LGR5+ pig model in exploring the role of LGR5+ cells in tissue development and regeneration with the goal of translating these findings into human and animal clinical applications.